Principle of proportionality and non-international armed conflicts - Valiollah Noori; Seyed Ghasem Zamani (Faṣlnāmah-i Pizhūhish-i Huqūq-i ̒Umūmī, 2018)
In the past, most armed conflicts were international, but today armed conflicts often are non-international and internal conflicts. However most of international armed conflicts rules are about international armed conflicts and some of them regulate non-international conflicts. Applicability of some of international humanitarian law rules to this kind of conflicts is doubtful. One of these rules is the principle of proportionality. This principle means that incidental and consequential damages resulting from an attack against civilians or civilian objects should not exceed the direct military advantage expected of the attack. 1977 Additional Protocol II to the 1949 Geneva Conventions which deals with the rules governing non-international conflicts has not referred to this principle. However, in accordance with what is discussed in this paper, the principle of proportionality is applicable to these conflicts.